2018
DOI: 10.1101/328104
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-coding AUG circRNAs constitute an abundant and conserved subclass of circles

Abstract: 16Circular RNAs (circRNAs) are a subset of non-coding RNAs (ncRNAs) previously considered as 17

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…LKPT evidenced in the present work also possesses a lysine amino acid residue in N-terminal position as it was also found in the minimal sequence from α-actinin-2 (KPYIL) able to stimulate the GLP-1 secretion in murine GLUTag cells. However, the K residue position in the sequence does not seem crucial for the bioactivity as ASDKPYIL is also active [51]. The RVASMASEKM peptide, recently identified from egg white protein digest as GLP-1 secretagogue, also possesses a K residue but in C-terminal position [48].…”
Section: Discussionmentioning
confidence: 99%
“…LKPT evidenced in the present work also possesses a lysine amino acid residue in N-terminal position as it was also found in the minimal sequence from α-actinin-2 (KPYIL) able to stimulate the GLP-1 secretion in murine GLUTag cells. However, the K residue position in the sequence does not seem crucial for the bioactivity as ASDKPYIL is also active [51]. The RVASMASEKM peptide, recently identified from egg white protein digest as GLP-1 secretagogue, also possesses a K residue but in C-terminal position [48].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the source, the understudied proteins could come from genomic mutations, alternative splicing, and noncoding RNA 8 . Translatable circRNAs play a role in lifting the veil of the 'ghost proteome' 9 . CircRNAs have been proposed to function in the assembly of complexes by competing with microRNAs (miRNAs) or RNA-binding proteins (RBPs) but have lost sight of their coding potential [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that particular circRNAs function as direct or indirect regulators of host gene expression at the transcriptional level [ 21 , 22 ], as sponges of microRNAs (miRNAs) [ 23 , 24 ], as protein scaffolds [ 25 ], or as specific or global regulators of protein translation [ 26 , 27 ]. Recent studies have reported that some circRNAs under certain circumstances can serve as templates for translation [ 28 , 29 , 30 , 31 ], yet the vast majority of circRNAs are considered to be non-coding [ 32 ]. See Figure 3 .…”
Section: Introductionmentioning
confidence: 99%